Manuver Mendelsohn sebagai terapi rehabilitasi pasien disfagia post-stroke - Insani, Nurul Fitri (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
Dysphagia can occur in geriatric patients and is found in post-stroke patients. Dysphagia is a swallowing disorder that can cause dehydration and disruption of daily activities. PSD is thought to be due to damage to the cortex and subcortical structures. After hospitalization, patients are expected to perform daily activities independently. The rehabilitative therapy that can be performed for post-stroke dysphagia patients is the Mendelsohn maneuver. The patient is asked to swallow food as usual, and when the food reaches the laryng, hold it up for 2-3 seconds with the throat muscles before finishing swallowing. Several studies have shown that there is an increased function in swallowing and a reduction in the incidence of aspiration.